2021
DOI: 10.1021/acs.jcim.1c00190
|View full text |Cite
|
Sign up to set email alerts
|

QM/MM Study of Human Transketolase: Thiamine Diphosphate Activation Mechanism and Complete Catalytic Cycle

Abstract: A computational model for Human transketolase was proposed showing that thiamine diphosphate activation was based on His110 in place of His481 reported in yeast TK. In addition, a complete catalytic reaction pathway was investigated using D-ylulose-5-phosphate and Dribose-5-phosphate as substrates showing at every step a perfect superimposition of our model with high resolution crystallographic structures 3MOS, 4KXV and 4KXX. This study shows that H2N4' of the active thiamine diphosphate "V form" no longer has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…The free energy activation barriers for acylation and deacylation steps were 20.0 and 15.1 kcal/mol, respectively. The energy profiles of human transketolase by QM/MM displayed that the reverse pathway has higher energy (79 kJ/mol) as compared to the forward reaction (50 kJ/mol) . Jafari et al investigated the catalytic reactions of myrosinase by wild-type and variants (E464A, Q187A, and Q187E) and showed that ascorbate ion might function as the general base in the wild-type enzyme if E464 and H141 are in their proper protonation states .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The free energy activation barriers for acylation and deacylation steps were 20.0 and 15.1 kcal/mol, respectively. The energy profiles of human transketolase by QM/MM displayed that the reverse pathway has higher energy (79 kJ/mol) as compared to the forward reaction (50 kJ/mol) . Jafari et al investigated the catalytic reactions of myrosinase by wild-type and variants (E464A, Q187A, and Q187E) and showed that ascorbate ion might function as the general base in the wild-type enzyme if E464 and H141 are in their proper protonation states .…”
Section: Discussionmentioning
confidence: 99%
“…The energy profiles of human transketolase by QM/MM displayed that the reverse pathway has higher energy (79 kJ/ mol) as compared to the forward reaction (50 kJ/mol). 78 Jafari et al investigated the catalytic reactions of myrosinase by wildtype and variants (E464A, Q187A, and Q187E) and showed that ascorbate ion might function as the general base in the wild-type enzyme if E464 and H141 are in their proper protonation states. 79 3α-hydroxysteroid dehydrogenase (3α-HSD) catalyzes 5α-dihydrotestosterone (5α-DHT) into 3αandrostanediol by proton transfer from Y55 without the formation of an alkoxide ion as an intermediate.…”
Section: ■ Discussionmentioning
confidence: 99%
“… 4 , 5 TKT mediates two reversible reactions in the non‐oxidative PPP: reversible conversion of R5P and xylulose‐5‐phosphate (Xu5P) to glyceraldehyde‐3‐phosphate (G3P) and sedoheptulose‐7‐phosphate (S7P), followed by conversion of Xu5P and erythrose‐4‐phosphate (E4P) to fructose‐6‐phosphate (F6P) and G3P. 6 …”
Section: Introductionmentioning
confidence: 99%
“…Transketolase (TKT) is a key rate‐limiting enzyme in the non‐oxidative branch of the pentose phosphate pathway (PPP), which produces more than 85% of ribose‐5‐phosphate (R5P), an important precursor for DNA and RNA biosynthesis 4,5 . TKT mediates two reversible reactions in the non‐oxidative PPP: reversible conversion of R5P and xylulose‐5‐phosphate (Xu5P) to glyceraldehyde‐3‐phosphate (G3P) and sedoheptulose‐7‐phosphate (S7P), followed by conversion of Xu5P and erythrose‐4‐phosphate (E4P) to fructose‐6‐phosphate (F6P) and G3P 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation